Analysis of Macroeconomic Influence on Economic Growth in Bali Province - Ramdani, Shinta; Arifin, Zainal (Jurnal Ilmu Ekonomi JIE, 2026)
This study analyzes the macroeconomic impact on economic growth in Bali Province using panel data regression for the 2019-2023 period. The variables studied include TPT, Gini Ratio, TPAK, and HDI on the GRDP ADHK of nine regencies/cities. The results show that all four variables have a significant simultaneous effect. Partially, TPT and Gini Ratio have a significant negative effect, and TPAK and HDI have a significant positive effect. TPAK has the largest impact on economic growth. These findings emphasize the importance of inclusive economic development through the creation of productive jobs, the improvement of human resource quality, and the reduction of income inequality.